Relationships between factors of ICT acceptance and usage among fishermen in Northern region of Peninsular Malaysia - Chhachhar, Abdul Razaque (2014)
Information communication technology (ICT) is playing very important role in enhancing the capacity building of different communities including fisheries sector by bringing positive impacts on the productivity and competitiveness. ICT promotes efficiency among the fishermen community through saving the time, energy and enhances information interactions and sharing. However, in Malaysian fishermen are still lagging behind in ICT development as compared to other sectors of the society. The selection of the independent variables for the use of ICT tools was based on the Unified Theory of Acceptance and Use of Technology (UTAUT) model. Moreover,the relationship between independent variables and use of ICT were also sought to determine the factors that have impact on the use of ICT tools by the fishermen community. Data collection was conducted by survey using self-administered questionnaires. A total of 200 respondents were randomly selected from Perak and Kedah states in Northern region of Peninsular Malaysia based on the highest number of registered fishermen. The data were analysed using Statistical Package for Social Sciences (SPSS) version 18 and the findings were presented using descriptive statistics and Pearson correlation. Findings of the study indicated that the level use of different ICT tools such as GPS,sonar, radar, wireless set and Echo sounder was moderate among the fishermen while the mobile phone usage was high in the fishermen community. Moreover, the use of mobile phones has the highest effect on different performance aspects of fishermen whereas echo sounder has the least effect. Moreover, others ICT tools have moderate effects on the performance expectancy of the fishermen. The use of mobile phones has also high effect on the efforts expectancy of the fishermen. However, expect GPS other ICT tools have moderate effects on different effort expectancy parameters of the fishermen. All the social influence variables of the ICT usage on the fishermen community indicated low effects on the fishermen. The facilitating conditions among respondents were moderate about their ownership of different ICT tools and availability of shops that provide sales and services of these tools. However, other ICT parameters showed low effect on the respondent fishermen. In conclusion the fishermen should be provided with the adequate information communication technologies along with proper knowledge and skills of the areas. Moreover, there is lack of trainings of ICT for the fishermen at their vicinities. Therefore, it is the responsibility of the government and other related agencies to make arrangements for the easy and cheap availability of ICT for the fishermen, they also should provide regular trainings and workshops on the usage and maintenance of different ICT such as computer, GPS, sonar, wireless set and other technologies to improve their lives and income.